An Ontology-Based Predictive Maintenance Tool for Power Substation Faults in Distribution Grid - Mahmoud M.A.; Tang A.Y.C.; Kumar K.; Law N.L.L.M.F.; Gurunathan M.; Ramachandran D. (Science and Information Organization, 2023)
3D modeling; Electric power transmission networks; Electric substations; Knowledge based systems; Maintenance; Ontology; Outages; Distribution grid; Failure prediction models; Hybrid simulation; Ontology's; Ontology-based; Power grids; Power substation fault; Power substations; Predictive maintenance; Simulation platform; Forecasting